The Yeast Telomere Length Counting Machinery Is Sensitive to Sequences at the Telomere-Nontelomere Junction - Ray, Alo (American Society for Microbiology, 1999)
Saccharomyces cerevisiae telomeres consist of a continuous 325 ± 75-bp tract of the heterogeneous repeat TG(1-3) which contains irregularly spaced, high-affinity sites for the protein Rap1p. Yeast cells monitor or count the number of telomeric Rap1p molecules in a negative feedback mechanism which modulates telomere length. To investigate the mechanism by which Rap1p molecules are counted, the continuous telomeric TG(1-3) sequences were divided into internal TG(1-3) sequences and a terminal tract separated by nontelomeric spacers of different lengths. While all of the internal sequences were counted as part of the terminal tract across a 38-bp spacer, a 138-bp disruption completely prevented the internal TG(1-3) sequences from being considered part of the telomere and defined the terminal tract as a discrete entity separate from the subtelomeric sequences. We also used regularly spaced arrays of six Rap1p sites internal to the terminal TG(1-3) repeats to show that each Rap1p molecule was counted as about 19 bp of TG(1-3) in vivo and that cells could count Rap1p molecules with different spacings between tandem sites. As previous in vitro experiments had shown that telomeric Rap1p sites occur about once every 18 bp, all Rap1p molecules at the junction of telomeric and nontelomeric chromatin (the telomere-nontelomere junction) must participate in telomere length measurement. The conserved arrangement of these six Rap1p molecules at the telomere-nontelomere junction in independent transformants also caused the elongated TG(1-3) tracts to be maintained at nearly identical lengths, showing that sequences at the telomere-nontelomere junction had an effect on length regulation. These results can be explained by a model in which telomeres beyond a threshold length form a folded structure that links the chromosome terminus to the telomere-nontelomere junction and prevents telomere elongation.